THE SPIRIT OF FREEDOM AGAINST DEHUMANIZATION IN FREDERICK DOUGLASS’ THE NARRATIVE LIFE OF FREDERICK DOUGLASS, AN AMERICAN SLAVE - Erna Cahyawati (Diterbitkan oleh Jurusan Sastra Indonesia Fakultas Ilmu Budaya Universitas Jember bekerja sama dengan Himpunan Sarjana - Kesusastraan Indonesia (HISKI), Himpunan Pembina Bahasa Indonesia (HPBI) dan Masyarakat Linguistik Indonesia (MLI), 2020)
American romanticism is a literary movement in the 19th century that upholds individualism, and freedom from all forms of confinement of convention, oppression or tyranny. This study focuses on abolitionism or the anti-slavery movement found in Frederick Douglass's autobiographical novel entitled The Narrative Life of Frederick Douglass, An American Slave. This study explores American romantic literature's characteristics in the book by capturing the dehumanization experienced by black American slaves and their spirit of resistance to the white oppression. The method used is the inductive method and descriptive method. The results showed that black people could gain confidence in striving for equality and freedom from white oppression by learning to read and write.